The Effect of Hot Water Treatment of Rooted Grapevine Nursery Stock on the Survival of the Root-knot Nematode, Meloidogyne javanica (Nematoda: Heteroderidae) - Knoetze, R. (South African Journal of Enology and Viticulture, 2020)
Root-knot nematodes (Meloidogyne spp.) are endoparasites which cause severe losses in grapevine. To ensure economically viable grape production, it is important that nurseries produce rooted nursery material free of plant-parasitic nematodes. Hot water treatment (HWT) at 50°C for 45 min to eliminate root-knot nematode (RKN) from rooted nursery material was investigated as a method to ensure nematode free plant material. Rooted grapevine rootstocks known to be susceptible (US 8-7 and 110 Richter), moderately resistant (1103 Paulsen and 143 B) and resistant (Ramsey) to Meloidogyne javanica were artificially infested by inoculating them with RKN eggs and larvae. After one growing season, the vines were lifted, shoots and root systems trimmed and subjected to different HWT regimes viz. 50°C for 45 min and 55°C for 20 min, while some were left as untreated controls. To evaluate plant response, each vine was planted in a pot, together with a three-week old tomato seedling as an indicator of root-knot nematode infestation. The tomato plants were removed after 12 weeks and their roots examined for the presence of M. javanica galls and egg masses. At the end of the growing season, the effects of the treatments on plant growth were assessed by determining total shoot and root mass. The results demonstrated that HWT at 55°C for 20 min significantly reduced the nematode populations in the rooted stocks, but did not eliminate the nematodes from the roots since indicator plants from HWT vines still supported a small number of galls. HWT at 55°C for 20 min also reduced the level of infestation of RKN in grapevine planting material, but resulted in a significant reduction in growth.